Phosphorus-doped graphite phase carbon nitride quantum dot and preparation method thereof

By doping hexachlorotripolyphosphazene in graphite phase carbon nitride quantum dots and calcining in a tube furnace, the fluorescence intensity and emission peak position of graphite phase carbon nitride quantum dots are significantly improved, and the problem of low fluorescence intensity in the existing technology is solved and its application prospects are broadened.

CN119503742APending Publication Date: 2025-02-25GUANGXI NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411731936.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing graphite phase carbon nitride quantum dots have low fluorescence intensity, narrow emission peak wavelength range, and low quantum yield, which limits its application prospects.

Method used

Hexachlorotripolyphosphazene is used as the phosphorus source, and the graphite phase carbon nitride quantum dots are calcined in a tube furnace, and argon is used for constant temperature reaction to prepare phosphorus-doped graphite phase carbon nitride quantum dots.

Benefits of technology

Through phosphorus doping, the fluorescence intensity of graphite phase carbon nitride quantum dots is enhanced by more than 1,200 times, the emission peak position is redshifted, and it has fluorescence behavior independent of the excitation wavelength. It is suitable for biological imaging, optoelectronic devices and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503742A_ABST
    Figure CN119503742A_ABST
Patent Text Reader

Abstract

The invention discloses phosphorus-doped graphite phase carbon nitride quantum dots and a preparation method thereof. The phosphorus-doped graphite phase carbon nitride quantum dots are prepared by taking graphite phase carbon nitride quantum dots as raw materials, hexachlorotripolyphosphazene as a phosphorus source and a tubular furnace as a reaction chamber through constant-temperature reaction in an argon atmosphere. According to the method, the phosphonitrilic chloride trimer is used as a phosphorus source, is insoluble in water and is easy to sublimate after being heated, the impurity removal problem does not need to be considered subsequently, and the operation is simple, convenient and safe; the phosphonitrilic chloride trimer is used as a phosphorus source, and an existing conventional tube furnace can be used as reaction equipment, so that the production cost is effectively reduced; furthermore, the reaction is carried out in an argon atmosphere, the phosphorus-doped carbon nitride quantum dots with greatly improved fluorescence intensity can be obtained, compared with graphite-phase carbon nitride quantum dots, the fluorescence intensity is enhanced by more than 1200 times, the main peak position is subjected to red shift, the emission peak of the phosphorus-doped graphite-phase carbon nitride quantum dots is 390nm, the sample size is uniform, and the fluorescence intensity of the phosphorus-doped graphite-phase carbon nitride quantum dots is greatly improved. The PL peak width of the phosphorus-doped graphite phase carbon nitride quantum dot is widened to 225 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to graphite phase carbon nitride quantum dots, in particular to phosphorus-doped graphite phase carbon nitride quantum dots and a preparation method thereof. Background Art

[0002] Graphitic carbon nitride quantum dots (GCNQDs) have shown good application prospects in bioimaging, optoelectronic devices, ion detection, photocatalysis, anti-counterfeiting and information encryption in recent years due to their excellent stability, good water solubility, biocompatibility, low toxicity and excellent optical properties.

[0003] The fluorescence intensity of graphite phase carbon nitride quantum dots prepared at present is very low, the emission peak wavelength range is narrow, and the quantum yield is also relatively low. These shortcomings limit the application of graphite phase carbon nitride quantum dots. Directly doping non-metallic elements in graphite phase carbon nitride quantum dots is a simple and easy strategy to change their structure and surface chemical properties, which can significantly improve the fluorescence intensity. Most of the methods that have been disclosed to improve the fluorescence intensity of graphite phase carbon nitride quantum dots are cumbersome and have a long preparation cycle, which is not conducive to rapid preparation.

[0004] The invention patent with publication number CN111808610A discloses "a carbon nitride-like phosphorus-rich quantum dot fluorescent probe and its preparation method and application". Specifically, it is synthesized from a phosphorus-rich monomer by a hydrothermal or solvothermal method under high pressure and high temperature, and then the obtained carbon nitride-like phosphorus-rich quantum dots are added to a 5000Da dialysis bag, dialyzed in pure water for three days, and finally the purified carbon nitride-like phosphorus-rich quantum dot fluorescent probe is obtained. Although this method is simple to operate, it is to dissolve the phosphorus source in a solvent, and then purify it, resulting in a long preparation cycle. Therefore, it is necessary to seek a method for preparing phosphorus-doped graphite phase carbon nitride quantum dots that takes into account simple operation, shortened experimental cycle, and low production cost. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a phosphorus-doped graphite phase carbon nitride quantum dot which is fast, simple, has low production cost and can greatly improve the fluorescence intensity of the carbon nitride quantum dot and a preparation method thereof.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing phosphorus-doped graphite phase carbon nitride quantum dots, which uses graphite phase carbon nitride quantum dots as raw materials, hexachlorotripolyphosphazene as a phosphorus source, uses a tubular furnace as a reaction chamber for calcination, and introduces argon gas to react at a constant temperature in an argon atmosphere to prepare the particles; Wherein, the mass ratio of hexachlorotripolyphosphazene to graphite phase carbon nitride quantum dots is 1-9:1.

[0007] In the preparation method of the present invention, preferably, the mass ratio of the hexachlorotripolyphosphazene to the graphite phase carbon nitride quantum dots is 6:1.

[0008] In the preparation method of the present invention, preferably, the mass ratio of the hexachlorotripolyphosphazene to the graphite phase carbon nitride quantum dots is 9:1.

[0009] In the preparation method of the present invention, the calcination temperature of the tubular furnace is 200-500° C. and the calcination time is 1-5 hours, so that the reaction is more complete.

[0010] In the preparation method of the present invention, the flow rate of the introduced argon gas is 30-70 ml / min, and the time of introducing the argon gas is 5-15 min.

[0011] In the preparation method of the present invention, hexachlorotripolyphosphazene is used as a phosphorus source, and an existing conventional tube furnace can be used as a reaction device for reaction. The applicant has improved the quartz glass tube of the existing tube furnace, specifically: the tube furnace includes a quartz glass tube, a pair of small porcelain boats that are buckled forward and backward are arranged inside, and quartz glass sleeves with valves are connected to both ends of the quartz glass tube to control the time of introducing argon gas and ensure that the experiment is carried out in an argon atmosphere; When in use, the graphite phase carbon nitride quantum dots are placed on one side of the upright small porcelain boat, and the hexachlorotripolyphosphazene is placed on the other side. The graphite phase carbon nitride quantum dots and the hexachlorotripolyphosphazene are placed alternately without direct contact. Then, another small porcelain boat is turned upside down on top of the upright small porcelain boat, tightly wrapped with tin foil, and placed in the center of the quartz glass tube.

[0012] By improving the quartz glass tube of the existing tubular furnace, connecting quartz glass sleeves with valves at both ends of the quartz glass tube and controlling the time of introducing argon gas, the yield of the sample can be increased to 45% to 50%.

[0013] Another object of the present invention is to provide phosphorus-doped graphite carbon nitride quantum dots prepared by the above-mentioned preparation method. Experiments have confirmed that the phosphorus-doped graphite carbon nitride quantum dots can greatly improve the fluorescence intensity of the graphite carbon nitride quantum dots as phosphorus is added. Compared with the graphite carbon nitride quantum dots, the fluorescence intensity of the phosphorus-doped graphite carbon nitride quantum dots is enhanced by more than 1200 times, and the main peak position is red-shifted. The emission peak of the phosphorus-doped graphite carbon nitride quantum dots is 390nm, and the PL emission peak hardly changes with the change of the excitation wavelength, indicating that the phosphorus-doped graphite carbon nitride quantum dots have PL behavior that is independent of the excitation wavelength, and the sample size is uniform, and the PL peak width of the phosphorus-doped graphite carbon nitride quantum dots is widened to 225nm.

[0014] The phosphorus-doped graphite-phase carbon nitride quantum dots prepared by the present invention have good application prospects in the fields of biological imaging, optoelectronic devices, ion detection, photocatalysis, anti-counterfeiting and information encryption.

[0015] Compared with the prior art, the method of the present invention uses hexachlorotripolyphosphazene as a phosphorus source. Compared with other phosphorus sources, hexachlorotripolyphosphazene is insoluble in water and easily sublimates when heated. During preparation, graphite phase carbon nitride quantum dots and hexachlorotripolyphosphazene are placed at intervals and are not in direct contact. There is no need to consider the problem of impurity removal later, and the operation is simple and safe. Moreover, using hexachlorotripolyphosphazene as a phosphorus source, an existing conventional tubular furnace can be used as a reaction device without special customization, and the production cost is effectively reduced. Furthermore, using hexachlorotripolyphosphazene as a phosphorus source and a tubular furnace as a reaction device for constant temperature reaction under an argon atmosphere can obtain phosphorus-doped carbon nitride quantum dots with greatly improved fluorescence intensity. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the structure of the tubular furnace quartz glass tube used in the preparation method of the present invention; In the figure, 1. quartz glass sleeve 2. quartz glass tube 3. porcelain boat.

[0017] Figure 2 This is the fluorescence spectrum of the phosphorus-doped carbon nitride quantum dots prepared in Example 2-5.

[0018] Figure 3 The fluorescence intensity comparison diagram (left figure) and fluorescence intensity growth multiple diagram (right figure) of phosphorus-doped carbon nitride quantum dots and graphite phase carbon nitride quantum dots prepared in Example 2-5; Figure 3 In the left figure, a represents graphite phase carbon nitride quantum dots, b represents embodiment 2, c represents embodiment 3, d represents embodiment 4, and e represents embodiment 5.

[0019] Figure 4 These are pictures of graphite phase carbon nitride quantum dots and Examples 4 and 5 under 265nm and 365nm ultraviolet light irradiation.

[0020] Figure 5 The ultraviolet-visible absorption spectra of graphite phase carbon nitride quantum dots and phosphorus-doped graphite phase carbon nitride quantum dots prepared in Example 2-5; In the figure, a represents graphite phase carbon nitride quantum dots, b represents embodiment 2, c represents graphite phase carbon nitride quantum dots 3, d represents embodiment 4, and e represents embodiment 5.

[0021] Figure 6 X-ray electron energy spectra of graphite phase carbon nitride quantum dots and phosphorus-doped graphite phase carbon nitride quantum dots prepared in Example 2-5. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with the embodiments and drawings for a better understanding of the present invention, but the present invention is not limited to the following embodiments. Example 1

[0023] The structure of the improved tubular furnace quartz glass tube of the present application is as follows: Figure 1 As shown, the tube furnace includes a long straight quartz glass tube 2, in which a pair of small porcelain boats 3 are arranged, and quartz glass sleeves 1 with valves are connected to both ends of the quartz glass tube 2 to control the time of introducing argon gas and ensure that the experiment is carried out in an argon atmosphere; When in use, the graphite phase carbon nitride quantum dots are placed on the left side of the upright small porcelain boat, and the hexachlorotripolyphosphazene is placed on the right side. The graphite phase carbon nitride quantum dots and the hexachlorotripolyphosphazene are placed at intervals without direct contact. Then, another small porcelain boat is turned upside down on top of the upright small porcelain boat, and wrapped tightly with tin foil and placed in the center of the quartz glass tube 2. Example 2

[0024] To prepare phosphorus-doped carbon nitride quantum dots, take 0.3g of hexachlorotripolyphosphazene and 0.3g of graphite phase carbon nitride quantum dots, put them into a small porcelain boat, wrap the small porcelain boat with tin foil, put it into the quartz glass tube of a tubular furnace, assemble the instrument, pass argon at a rate of 30-70ml / min for 5-15min, then close the valves at both ends, calcine at 200-500℃ for 1-5h under argon atmosphere, and naturally cool to room temperature after the reaction to obtain phosphorus-doped graphite phase carbon nitride quantum dots. Example 3

[0025] Take 0.9 g of hexachlorotripolyphosphazene and 0.3 g of graphite-phase carbon nitride quantum dots, and follow the same other steps as in Example 2 to prepare phosphorus-doped graphite-phase carbon nitride quantum dots. Example 4

[0026] Take 1.8 g of hexachlorotripolyphosphazene and 0.3 g of graphite-phase carbon nitride quantum dots, and follow the same other steps as in Example 2 to prepare phosphorus-doped graphite-phase carbon nitride quantum dots. Example 5

[0027] Take 2.7 g of hexachlorotripolyphosphazene and 0.3 g of graphite-phase carbon nitride quantum dots, and follow the same other steps as in Example 2 to prepare phosphorus-doped graphite-phase carbon nitride quantum dots.

[0028] The fluorescence intensity of the graphite phase carbon nitride quantum dots and the phosphorus-doped graphite phase carbon nitride quantum dots of Examples 2-5, and the fluorescence intensity growth multiples are shown in the following table:

[0029] As can be seen from the above table, with the incorporation of phosphorus, the fluorescence intensity gradually increases, and the fluorescence intensity enhancement of Examples 4 and 5 is particularly significant. Compared with graphite phase carbon nitride quantum dots, the fluorescence intensity of phosphorus-doped graphite phase carbon nitride quantum dots prepared in Examples 4 and 5 is enhanced by more than 1200 times.

[0030] XPS content detection was performed on the carbon content, phosphorus content, etc. in the phosphorus-doped graphite phase carbon nitride quantum dots prepared in Example 2-5, and the results are shown in the following table:

[0031] As can be seen from the above table, graphite phase carbon nitride quantum dots are composed of three elements: C, N, and O. Examples 2-5 are composed of four elements: C, N, O, and P. The surface P element is successfully incorporated into the structure of graphite phase carbon nitride quantum dots, and P atoms replace part of the C atoms in the graphite phase carbon nitride quantum dots, resulting in a significant enhancement in the fluorescence intensity of the graphite phase carbon nitride quantum dots.

[0032] The phosphorus-doped graphite phase carbon nitride quantum dots prepared in Examples 2-5 were subjected to fluorescence testing, and their fluorescence emission peaks and fluorescence intensities were as follows: Figure 2 As shown. Figure 2 It can be seen that with the incorporation of phosphorus, the fluorescence intensity of graphite phase carbon nitride quantum dots can be greatly improved, and the main peak position is red-shifted. The fluorescence intensity of Examples 4 and 5 is significantly stronger than that of Examples 2 and 3. Compared with graphite phase carbon nitride quantum dots, the fluorescence intensity of phosphorus-doped graphite phase carbon nitride quantum dots prepared in Examples 4 and 5 is enhanced by more than 1200 times.

[0033] According to the fluorescence spectra of the graphite phase carbon nitride quantum dots and the phosphorus-doped graphite phase carbon nitride quantum dots prepared in Example 2-5, a fluorescence intensity comparison diagram and a fluorescence intensity growth multiple diagram were drawn, as shown in FIG. Figure 3 As shown. Figure 3 It can be seen that compared with graphite phase carbon nitride quantum dots, the main peak positions of Examples 4 and 5 are red-shifted, and the fluorescence intensity of Examples 4 and 5 is enhanced by a thousand times compared with graphite phase carbon nitride quantum dots.

[0034] The graphite phase carbon nitride quantum dots and the phosphorus-doped graphite phase carbon nitride quantum dots prepared in Example 4 and Example 5 are shown in Figure 1 under 265nm and 365nm ultraviolet light. Figure 4 As shown. Figure 4 It can be seen that the fluorescence of the graphite phase carbon nitride quantum dot aqueous solution under ultraviolet light is very weak and almost invisible to the naked eye. After phosphorus doping, the luminescent color is different under different ultraviolet light irradiation, and the luminescence is very strong. Compared with the graphite phase carbon nitride quantum dots, the fluorescence intensity of the phosphorus-doped graphite phase carbon nitride quantum dots prepared in Examples 4 and 5 is enhanced by more than 1200 times.

[0035] The graphite phase carbon nitride quantum dots and the phosphorus-doped graphite phase carbon nitride quantum dots prepared in Example 2-5 were analyzed by a UV-visible photometer. Their UV-visible absorption spectra are as follows: Figure 5 As shown. Figure 5It can be seen that the absorption edges of Example 4 and Example 5 are red-shifted, corresponding to the red-shift of the main peaks of the fluorescence spectra of Example 4 and Example 5.

[0036] The graphite phase carbon nitride quantum dots and the phosphorus-doped graphite phase carbon nitride quantum dots prepared in Example 2-5 were analyzed by an X-ray electron spectrometer. Their X-ray electron spectra are as follows: Figure 6 As shown. Figure 6 It can be seen that the raw material graphite phase carbon nitride quantum dots have obvious carbon peaks, nitrogen peaks and oxygen peaks at 289eV, 400eV and 532eV, while the phosphorus-doped carbon nitride quantum dots prepared in the embodiment have obvious carbon peaks, nitrogen peaks and oxygen peaks, as well as an obvious phosphorus peak at 133eV, indicating that phosphorus atoms have been successfully doped into the graphite phase carbon nitride quantum dots.

Claims

1. A method for preparing phosphorus-doped graphite phase carbon nitride quantum dots, characterized in that: The method is to use graphite phase carbon nitride quantum dots as raw materials, hexachlorotripolyphosphazene as phosphorus source, use a tubular furnace as a reaction chamber for calcination, and introduce argon gas to react at a constant temperature in an argon atmosphere. The mass ratio of hexachlorotripolyphosphazene to graphite phase carbon nitride quantum dots is 1-9:

1.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the hexachlorotripolyphosphazene to the graphite phase carbon nitride quantum dots is 6:

1.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the hexachlorotripolyphosphazene to the graphite phase carbon nitride quantum dots is 9:

1.

4. The preparation method according to claim 1, characterized in that: The calcination temperature in the tubular furnace is 200-500° C., and the calcination time is 1-5 hours.

5. The preparation method according to claim 1, characterized in that: The flow rate of the introduced argon gas is 30-70 ml / min, and the time of introducing argon gas is 5-15 min.

6. The preparation method according to claim 1, characterized in that: The tube furnace includes a quartz glass tube, in which a pair of small porcelain boats are arranged, and quartz glass sleeves with valves are connected to both ends of the quartz glass tube to control the time of introducing argon gas and ensure that the experiment is carried out in an argon atmosphere; When in use, the graphite phase carbon nitride quantum dots are placed on one side of the upright small porcelain boat, and the hexachlorotripolyphosphazene is placed on the other side. The graphite phase carbon nitride quantum dots and the hexachlorotripolyphosphazene are placed alternately without direct contact. Then, another small porcelain boat is turned upside down on top of the upright small porcelain boat, tightly wrapped with tin foil, and placed in the center of the quartz glass tube.

7. The phosphorus-doped graphite-phase carbon nitride quantum dots prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The phosphorus-doped graphite carbon nitride quantum dots can greatly improve the fluorescence intensity of the graphite carbon nitride quantum dots as phosphorus is doped. Compared with the graphite carbon nitride quantum dots, the fluorescence intensity of the phosphorus-doped graphite carbon nitride quantum dots is enhanced by more than 1200 times, and the main peak position is red-shifted. The emission peak of the phosphorus-doped graphite carbon nitride quantum dots is 390nm, and the PL emission peak hardly changes with the change of the excitation wavelength, indicating that the phosphorus-doped graphite carbon nitride quantum dots have PL behavior that is independent of the excitation wavelength, and the sample size is uniform, and the PL peak width of the phosphorus-doped graphite carbon nitride quantum dots is widened to 225nm.

Citation Information

Patent Citations

  • Carbon nitride-like phosphorus-rich quantum dot fluorescent probe, and preparation method and application thereof

    CN111808610A